2022 Brazilian Thoracic Association recommendations for long-term home oxygen therapy - de Oliveira Castellano, Maria Vera Cruz; Pereira, Luiz Fernando Ferreira; Feitosa, Paulo Henrique Ramos; Knorst, Marli Maria; Salim, Carolina; Rodrigues, Mauri Monteiro; Ferreira, Eloara Vieira Machado; de Menezes Duarte, Ricardo Luiz; Togeiro, Sonia Maria; Stanzani, Lícia Zanol Lorencini; Júnior, Pedro Medeiros; de Melo Schelini, Karime Nadaf; et al. (Sociedade Brasileira de Pneumologia e Tisiologia, 2022)
Some chronic respiratory diseases can cause hypoxemia and, in such cases, long-term home oxygen therapy (LTOT) is indicated as a treatment option primarily to improve patient quality of life and life expectancy. Home oxygen has been used for more than 70 years, and support for LTOT is based on two studies from the 1980s that demonstrated that oxygen use improves survival in patients with COPD. There is evidence that LTOT has other beneficial effects such as improved cognitive function, improved exercise capacity, and reduced hospitalizations. LTOT is indicated in other respiratory diseases that cause hypoxemia, on the basis of the same criteria as those used for COPD. There has been an increase in the use of LTOT, probably because of increased life expectancy and a higher prevalence of chronic respiratory diseases, as well as greater availability of LTOT in the health care system. The first Brazilian Thoracic Association consensus statement on LTOT was published in 2000. Twenty-two years later, we present this updated version. This document is a nonsystematic review of the literature, conducted by pulmonologists who evaluated scientific evidence and international guidelines on LTOT in the various diseases that cause hypoxemia and in specific situations (i.e., exercise, sleep, and air travel). These recommendations, produced with a view to clinical practice, contain several charts with information on indications for LTOT, oxygen sources, accessories, strategies for improved efficiency and effectiveness, and recommendations for the safe use of LTOT, as well as a LTOT prescribing model.
Recomendações para oxigenoterapia domiciliar prolongada da Sociedade Brasileira de Pneumologia e Tisiologia (2022)
Keywords: Delivery of health care; Hypoxia; Oxygen; Oxygen inhalation therapy